Substantiating optimal technological parameters of granite block extraction with reference to jointing indicators - Левицький, Володимир Григорович; Соболевський, Руслан Вадимович (Eastern-European Journal of Enterprise Technologies, 2014)
The algorithm of forming technological complexes at facing stone quarries was elaborated. It includes designating structural-homogeneous and structural-technological quarry zones and determining the optimal technological parameters for them. The dependence of stone losses while preparing a monolith for separating by diamond-yarding units on the size of the monolith was studied in order to establish the main factors, affecting the coefficient of losses and estimate optimum length and height of the monolith. It was found that with the height and length of the monolith amounting to less than 2 m, the loss coefficient value increases drastically. Basing on the initial data of the spatial orientation of joints and the dependencies, set by the criterion of minimizing block production losses, for the conditions of the Nataliivskiy granodiorite deposit the optimal technological parameters of blocks extraction were identified as follows: the bench height equals to 5.815 m, the monolith width is 1.34 m, the length amounts to 5 m. The obtained results allow optimizing the structural-technological career area parameters and increasing the production of high-quality commercial output.